Effect of Green Lean Body Capsules on Body Weight, Lipid Profile, and Renal Physiology and Histology in Albino Rats - Makarim Q. Al-Lami (مجلة كلية الطب, 2015)
Background: Many anti-obesity medicines have been increased in recent years to solve the problem of obesity; among these medicines are Green Lean Body Capsules (GLBCs) which contain green plants and fruits extract. Objective: This study was designed to evaluate the effects of daily oral consumption of GLBCs on level of serum lipids, renal function tests, and the histological structure of the kidney in albino rats. Materials and Methods: Twenty adult albino male rats weighing 240-260 g were divided into 2 equal groups: control group and GLBCs-treated group. During the 4-weeks treatment, each rat in the GLBCs-treated group was orally administered with 20 mg/kg B.W. of GLBCs, while the control rats were orally administered with 0.1 ml D.W. Body weights were monitored at the beginning and at the end of the experimental period. Lipid profile [total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), very lowdensity lipoprotein cholesterol (VLDL-C) and low-density lipoprotein cholesterol (LDL-C)], renal function tests (blood urea and serum creatinine) ; in addition to the histological examination of the kidney were evaluated in all the rats. Results: The results revealed that body weight gain was significantly (P<0.05) less in the GLBCs-treated rats than in the control rats. Results of the lipid profile showed that the levels of TC, TG, LDL-C and VLDL-C were significantly (P<0.05) lower while the level of HDL-C was significantly (P < 0.05) higher in the GLBCs-treated rats than that in the control rats. Regarding the renal function tests, the results revealed that blood urea and serum creatinine levels in the GLBCs-treated rats were significantly (P<0.05) lower than that in the control rats. However, microscopic examination of the kidney revealed that both the control and the GLBCs-treated groups presented similar type of histological manifestations. Conclusion: The data presented in this study suggested that the compounds found in GLBCs may act synergistically to suppress body weight gain, decrease the level of serum lipids, and decrease the level of renal function tests without any histological abnormalities effect in the kidney.